Circular-based economy and female entrepreneurship in rural tourism communities: a research agenda - Velázquez-Castro, Judith Alejandra; Cruz Coria, Erika; Calanchez Urribarri, África Del Valle (Revista Venezolana de Gerencia, 2025)
This study addresses the critical intersection of female entrepreneurship and the circular economy within rural communities, a topic that has received limited systematic attention in academic literature. Rural areas often present unique socioeconomic and demographic challenges, including limited social and economic interaction, which can hinder the growth and sustainability of businesses, particularly those led by women. While existing research has explored the broader relationship between entrepreneurship and sustainability, a significant gap remains in studies that specifically systematize the convergence of the circular economy and female entrepreneurship. To bridge this gap, a comprehensive theoretical review was conducted, drawing exclusively from a corpus of scientific articles on the subject. The results show three important findings. First, the principles of the circular economy—such as reducing, reusing, and recycling resources—are highly compatible with the tourism sector, especially in rural settings where sustainable practices can create unique value propositions. Second, the review identified several benefits and best practices of a circular tourism economy, highlighting how these models can enhance resource efficiency and foster local economic resilience. Finally, the study outlined the significant challenges that female entrepreneurs face in adopting these models, including access to capital, networks, and specialized knowledge. Building on these insights, this research also proposes a set of strategic recommendations, aimed at not only to offer new opportunities for female entrepreneurs in rural areas but also to contribute directly to the objectives outlined in the 2030 Agenda for Sustainable Development, particularly those focused on gender equality and responsible consumption and production.